DNA binding properties of the Arabidopsis floral development protein AINTEGUMENTA - Nole-Wilson, Staci (Oxford University Press, 2000)
The Arabidopsis protein AINTEGUMENTA (ANT) is a member of a plant-specific family of transcription factors (AP2/EREBP) that share either one or two copies of an approximately 70 amino acid region called the AP2 repeat. DNA binding activity has been demonstrated previously for members of this family containing a single AP2 repeat. Using an in vitro selection procedure, the DNA binding specificity of the two AP2 repeat containing protein ANT was found to be 5′-gCAC(A/G)N(A/T)TcCC(a/g)ANG(c/t)-3′. This consensus site is much longer than sites recognized by proteins containing a single AP2 repeat and neither AP2 repeat of ANT was alone capable of binding to the selected sequences, suggesting that both AP2 repeats make DNA contacts. ANT binds to these DNA sequences as a monomer but a higher order complex is also observed at high protein concentrations. The  ANT consensus site shows some similarity to the C-repeat/DRE elements bound by proteins that contain a single AP2 repeat, and we find that ANT binds weakly to such sites. We propose a model in which each AP2 repeat of ANT contacts adjacent sites within the consensus sequence. Our results suggest that the AP2 repeat can be utilized in different ways for DNA binding.